2006
DOI: 10.1074/jbc.c600231200
|View full text |Cite
|
Sign up to set email alerts
|

First Structure of a Eukaryotic Phosphohistidine Phosphatase

Abstract: Phosphatases are a diverse group of enzymes that regulate numerous cellular processes. Much of what is known relates to the tyrosine, threonine, and serine phosphatases, whereas the histidine phosphatases have not been studied as much. The structure of phosphohistidine phosphatase (PHPT1), the first identified eukaryotic-protein histidine phosphatase, has been determined to a resolution of 1.9 Å using multiple-wavelength anomalous dispersion methods. This enzyme can dephosphorylate a variety of proteins (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
(28 reference statements)
1
29
1
Order By: Relevance
“…In the first crystal structure of hPHPT1 (PDB code: 2HW4), five formate ions bind to the protein at a relatively large area near residues Lys 21 , His 53 and Arg 78 [12]. It was proposed that His 53 plays a major role in the enzyme activity, and the positively charged side chains of residues Lys 21 and Arg 78 serve as anchors of the substrate as well as helping to stabilize the charge of transition state in the catalysis reaction, based on the structure and mutagenesis results [12]. However, the fact that the R78A mutation only results in ∼ 2-fold decrease in enzyme activity does not really support its role as a substrate anchor.…”
Section: Introductionmentioning
confidence: 99%
“…In the first crystal structure of hPHPT1 (PDB code: 2HW4), five formate ions bind to the protein at a relatively large area near residues Lys 21 , His 53 and Arg 78 [12]. It was proposed that His 53 plays a major role in the enzyme activity, and the positively charged side chains of residues Lys 21 and Arg 78 serve as anchors of the substrate as well as helping to stabilize the charge of transition state in the catalysis reaction, based on the structure and mutagenesis results [12]. However, the fact that the R78A mutation only results in ∼ 2-fold decrease in enzyme activity does not really support its role as a substrate anchor.…”
Section: Introductionmentioning
confidence: 99%
“…The GST-KCa3.1(CT) was phosphorylated by NDPK-B by using [␥-32 P]GTP as described (3). His-PHPT-1(WT) or His-PHPT-1(H53A) were expressed in the expression vector pET-28 in Escherichia coli and purified as described (3,8). Dephosphophorylation was assessed after the addition of His-PHPT-1(WT) or His-PHPT-1(H53A) (2.5 mg per reaction) to the same reaction for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, PHPT1 probably plays an important biological role. Recent site-specific mutagenesis and crystallography studies have revealed the three-dimensional structure of PHPT1 and provided information about its active site (Busam et al 2006;Ma et al 2005). In order to determine the solution structure and study its interaction with substrate proteins, we herein report the nearly complete sequencespecific backbone and side-chain NMR assignments of human PHPT1.…”
mentioning
confidence: 98%